A Facile One‐Pot Synthesis of 1, 2, 3, 4‐Tetrahydroisoquinoline‐1‐carbonitriles via the Electrogenerated Cyanide Anions from Acetonitrile. Issue 15 (17th April 2020) - Sbei, Najoua; Titov, Alexander A.; Markova, Ekaterina B.; Elinson, Michail N.; Voskressensky, Leonid G.
Abstract: The electrosynthesis of 1, 2, 3, 4‐tetrahydroisoquinoline‐1‐carbonitriles by acetonitrile reduction is a green and safe strategy to replace the traditional cyanation. Herein, we have obtained the 1, 2, 3, 4‐tetrahydroisoquinoline‐1‐carbonitrile in good yields by a simple reaction between dihydroisoquinolin‐2‐ium iodide and the electrogenerated acetonitrile formed under low temperature conditions, when a solution of dry acetonitrile is electrolyzed at a Carbon rod as cathode and a magnesium plate as anode in undivided cell. Abstract : Herein new and facile synthesis of 1, 2, 3, 4‐tetrahydroisoquinoline‐1‐carbonitriles derivatives with different substituents was presented in good yields. This is a new simple, fast and no toxic way for the direct cyanation of dihydroisoquinolin‐2‐ium iodide by the electroreduction of acetonitrile. The reaction was performed in undivided cell under low temperature conditions using a Carbon rod as cathode and a magnesium plate as anode.